Abdominal wall surgery : how reimbursement systems can change surgical evolution - Greco, Dalila Patrizia; Borgonovi, Elio 1946- (Springer, 2019)
This book presents different patient-oriented perspectives from surgeons, economic evaluation and management researchers, and business companies active in the healthcare sector, striking a balance between the appropriateness/effectiveness of treatment and efficiency/cost. It does not include technical surgical details, but instead provides the necessary knowledge regarding different groups of patients to help economic and management researchers make accurate evaluations. Although partially based on the specific case of abdominal wall surgery in the Italian health system, the book defines a model that can, with the necessary adaptations, be applied in other national contexts. It also analyzes different reimbursement systems and methods of data collection. This approach supports the evolution from evidence-based medicine (EBM) to the future of real-world data (big data analysis). Further, it highlights the critical issue of "silos" reimbursement, which is the pillar ofDRG, and proposes methodology to evaluate the direct and indirect benefit and costs of surgery (for example quality of care, costs incurred in cases of surgical complications due to the use of inappropriate, low-cost material or due to surgical procedure. It is a valuable resource for clinicians, surgeons, policymakers and managers in the field.